KNOWLEDGE OF FEMALE ABOUT CERVICAL CANCER AND IVA TEST AT PUSKESMAS TIBAN BARU - Dino Gagah Prihadianto; Ade Ricky Harahap (Universitas Batam, 2021)
Background : According to WHO, cervical cancer is the second cancer after breast cancer which causes the death of women in the world. In Indonesia, more than 26 women die every day, because within three years about 42,000 died. For every screening out of 1,000 people, there is 1 woman who develops cervical cancer. Early detection coverage in Indonesia is less than five percent. This study aims to determine the knowledge of women of childbearing age and IVA Test. Method : The design in this study was cross sectional, namely to determine the relationship between the knowledge of women of childbearing age about cervical cancer with IVA test. The location of this research was at the puskesmas Tiban Baru and was carried out for 6 months. The population in this study were fertile aged women in the working area of Puskesmas Tiban Baru. The sample of this study used purposive sampling with a total sample of 61 respondents. This study uses bivariate data analysis with Chi Square statistical test. Result :The results of the study were obtained from 61 respondents, the majority of which had sufficient knowledge as many as 43 people (71%). And most of them performed IVA test as many as 45 people (74%), from the bivariate analysis obtained a p-value of 5 0.005, conclusion : there is a significant relationship between the knowledge of women of childbearing age about cervical cancer to the IVA examination. Suggestions to respondents are expected to be able to increase knowledge about cervical cancer and routinely carry out cervical cancer early detection checks by means of IVA examinations at health centers or health facilities that provide IVA Test